Do Changes in Employment and Hours Worked Contribute to a Decreasing in the Mental Health of Single Mothers during a Period of Welfare Reform in the UK? A Longitudinal Analysis (2009-2019) - Julija Simpson; Clare Bambra; Heather Brown (Institute of Labor Economics (IZA), 2021)
We investigate the role of employment in explaining changes in the mental health of single mothers compared to partnered mothers and single childless women during the period of welfare reform in the UK. We employ a time allocation framework to explore if reductions in benefit income led to a sub-optimal consumption bundle, resulting in lower in mental health, higher employment, and longer working hours. We estimate a Heckman selection model for employment and hours worked. A difference-in-difference model is used to explore if reform periods were associated with increased inequalities. Results show that employment was associated with better mental health for all women. Higher job hours were associated with lower mental health for all women but the association was not statistically significant for single mothers. Mental health inequalities potentially have increased post reforms.
Keywords: D13; I14; I38; J22; 330; welfare reform; employment; low-income; single mothers; mental health